Effect of salbutamol on histamine induced bronchoconstriction in healthy infants. Issue 4 (April 1993) - Henderson, A J; Young, S; Stick, S M; Landau, L I; LeSouëf, P N
Abstract : BACKGROUND--The effect of inhaled beta 2 adrenergic drugs on infants with wheezing disorders remains controversial. Salbutamol inhibits the bronchial responsiveness of infants to histamine and nebulised water but whether or not it acts as a bronchodilator in this age group is unclear. The aim of the present study was to determine whether salbutamol can hasten the reversal of histamine induced bronchoconstriction in infants. METHODS--Bronchial challenge with histamine was performed in 40 infants aged 12 months or less with no previous history of respiratory symptoms. Response to histamine was assessed by forced partial expiratory flow/volume curves to measure maximal flow at functional residual capacity (VmaxFRC). After a fall of 40% or more from baseline VmaxFRC, each infant was randomly assigned to receive either salbutamol 0.5% or saline 0.9% solution by nebuliser. The rate of recovery of VmaxFRC and the time to reach baseline VmaxFRC were derived by linear regression. RESULTS--Infants who received salbutamol had a significantly faster rate of recovery (geometric mean 8.5 ml/s/min) than those who received saline (4.1 ml/s/min). Considerable interindividual variation was observed in the time from maximum bronchoconstriction to recovery of baseline VmaxFRC in both groups of subjects. CONCLUSIONS--Salbutamol significantly speeds the reversal of histamine induced bronchoconstriction in infants during the first 12 months of life. This observation provides further evidence to support the presence of functional beta adrenergic receptors in the airways of infants.